A comparative study on infusion of usual dose of oxytocin and 80 units dose of oxytocin in the prevention of postpartum hemorrhage in cesarean section - Fatemeh Ahmadi (Wolters Kluwer Medknow Publications, 2018)
Postpartum hemorrhage is one of the main causes of mothers' death mostly in developing country. The frequency of postpartum hemorrhage after natural pregnancy and cesarean are reported 2%-4% and 6%, respectively. The main goal of this study is to compare two regimens of oxytocine: One with high dose and the other with normal one to prevent uterine atony. The study has been done via a clinical trial method on 150 pregnant women in Zahedan, Iran. The society is randomly divided into two groups. The patients having risk factors of uterine atony and postpartum hemorrhage were omitted from the list. Oxytocin with 80 and 30 dose was, respectively, infused in 500 cc Ringer serum for control and witness group immediately after infant emersion during a period of 30 min. Decline of hemoglobin 6 and 24 h after cesarean section, uterine atony, blood infusion, and extra uterotonic drug needs after oxytocin infusion have been measured for both groups. The data have been analyzed using Chi-square via SPSS software. The result indicates that there exist meaningful differences between control and witness group in uterine atony and extra utertonic drug need while and after surgery (0 as compared with 22.6% and P= 0); whereas there is no significant difference between control and trial group in decline of hemoglobin 6 and 24 h after cesarean section (P = 0.714 and 0.231, respectively). It means that oxytocin infusion with 80 dose has a good impact on the above four variances. It is recommended that oxytocin infusion with 80 dose during a period of 30 min could be a good substitution for oxytocin infusion with 30 dose for the prevention of uterine atony during and after cesarean delivery, especially when utertonic drug is not accessible and in the case of counterindication of other drugs' use.